REPRESENTASI KESETARAAN GENDER DALAM UNDANG-UNDANG PEMILU SERTA PENERAPANNYA BAGI PEREMPUAN BALI - Adi Widnyana, I Made (Institut Hindu Dharma Negeri Denpasar, 2020)
The purpose of this paper is to see the extent to which the Election Law is able to address gender equality in politics and democracy and how Balinese women apply this provision as an opportunity to advance and align themselves in the political field by looking at the results of the elections in Bali. So based on that research method used is normative research that refers to the provisions of applicable regulations and is supported by sources of literature and supporting data.It is known that the Election Law requires a 30% quota requirement for women's representation in the electoral process of each political party. This will be an opportunity for women to be able to align themselves and dilute the backwardness of men who used to dominate, although it is known that this cannot be said to be equal or balanced, but at least women are guaranteed their opportunity to be certain in politics through opportunities chosen rights they have.Balinese women from the results of the implementation of the 2004 legislative elections to 2019 for women's representation in the Bali Provincial DPRD, were able to show a significant increase in representation, so it can be said that Balinese women from time to time are able to take advantage of opportunities and opportunities to participate in the political and democratic equalization.